Silicone-based resin composition and semiconductor device comprising the same
Patent Information
- Application Number
- CN202480088640.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2026-09-25
AI Technical Summary
根据本发明的硅酮基树脂组合物包括其中一次颗粒团聚的颗粒状二次颗粒作为第一导热填料,并且所述第一导热填料的比表面积与平均粒径之比大于0.3且小于3.0。
Smart Images

Figure CN122826285A_ABST
Abstract
Description
[Technical Field] This invention relates to silicone-based resin compositions and semiconductor devices comprising the silicone-based resin compositions. [Background Technology] Since most electronic components generate heat during their use, it is necessary to remove this heat from them in order for them to function properly. In particular, the heat generated by integrated circuit components such as CPUs in personal computers is increasing due to their higher operating frequencies, making thermal management a critical issue.
[0003] Therefore, many methods for dissipating heat have been proposed, and for electronic components that dissipate a large amount of heat, methods have been proposed for dissipating heat by placing thermally conductive materials, such as thermal grease or thermal pads, between the electronic component and components such as heat sinks.
[0004] Korean Patent Application Publication No. 10-2020-0086307 discloses a semiconductor device including a thermally conductive material.
[0005] [Related Technical Documents] [Patent Documents] (Patent Document 1) Korean Patent Application Publication No. 10-2020-0086307 [Summary of the Invention] [Technical Issues] Therefore, the present invention was made in view of the above-mentioned problems, and one object of the present invention is to provide a silicone-based resin composition that can minimize thermal conductivity deviation and provide excellent heat dissipation performance due to improved coverage; and a semiconductor device comprising the silicone-based resin composition.
[0006] [Technical Solution] According to one aspect of the present invention, the above and other objects can be achieved by providing a silicone-based resin composition comprising: an organopolysiloxane; a first thermally conductive filler; and a curing catalyst, wherein the first thermally conductive filler comprises secondary particles in which the primary particles are agglomerated, and wherein the first thermally conductive filler satisfies the following formula 1: [Formula 1] 0.3 <A(m 2 / g) / B(µm)<3.0 Where A represents the specific surface area of the first thermally conductive filler and is a unitless value, and B represents the average particle size (D) of the first thermally conductive filler. 50 And it is a unitless value.
[0007] In one embodiment of the present invention, the primary particles may be flake-shaped particles.
[0008] In one embodiment of the invention, the first thermally conductive filler may have an aspect ratio of 0.5 to 3.
[0009] In one embodiment of the present invention, the first thermally conductive filler may have a content of 0.5 g / cm³. 3 Up to 6 g / cm 3 The tap density.
[0010] In one embodiment of the present invention, the silicone-based resin composition may further include a spherical second thermally conductive filler that is different from the first thermally conductive filler.
[0011] In one embodiment of the invention, the second thermally conductive filler may have an aspect ratio of 1 to 1.5.
[0012] In one embodiment of the present invention, the weight ratio of the first thermally conductive filler to the second thermally conductive filler may be 1:1 to 1:5.
[0013] In one embodiment of the invention, the lap shear strength of the silicone-based resin composition, as measured by DIN EN 1465, is 1 N / mm. 2 Or larger.
[0014] In one embodiment of the invention, the coverage of the silicone-based resin composition, as measured by the following measurement method 1, can be 90% or greater: [Measurement Method 1] 1) The silicone-based resin composition is coated at a weight of 0.7 g onto a first silicone substrate having dimensions of 27 mm × 27 mm. 2) Place a second silicone substrate having the same or larger dimensions as the first silicone substrate onto the coated silicone-based resin composition, and then allow the silicone-based resin composition to cure under a compressive force of 3 kgf. 3) Derive the area where the first silicone substrate is in close contact with the second silicone substrate by the cured silicone-based resin composition, and 4) The coverage rate is the ratio of the area of the first silicone substrate and the second silicone substrate in close contact to the planar area of the first silicone substrate.
[0015] In one embodiment of the present invention, the rate of change of thermal conductivity of the silicone-based resin composition, as measured by the following measurement method 2, is less than 30%: [Measurement Method 2] 1) The silicone-based resin composition was subjected to a temperature of 165°C and a pressure of 10 kgf / cm². 2The first sheet was produced by hot pressing under pressure for 15 minutes, and the silicone-based resin composition was separately subjected to heat treatment at 165°C and 0.1 kgf / cm². 2 The second sheet is manufactured by hot-pressing under pressure for 15 minutes. 2) The first sheet and the second sheet are cured at 150°C for 2 hours to produce a first sheet sample and a second sheet sample, respectively. 3) The thermal conductivity of the first sheet sample and the thermal conductivity of the second sheet sample were measured at 25°C according to ISO 22007-2. 4) Calculate the rate of change of thermal conductivity using the following formula 2: [Formula 2] Rate of change of thermal conductivity (%) = (|TC) 10 – TC 0.1 │ / TC 10 ) × 100 Among them TC 10 It is the thermal conductivity (W / mK) of the first sheet sample, and TC 0.1 It is the thermal conductivity (W / mK) of the second sheet sample.
[0016] According to another aspect of the present invention, a semiconductor device is provided, comprising: a semiconductor package; a heat dissipation portion disposed on the semiconductor package; and a thermally conductive layer disposed between the semiconductor package and the heat dissipation portion, wherein the thermally conductive layer comprises a silicone-based resin composition, wherein the silicone-based resin composition comprises an organopolysiloxane, a first thermally conductive filler, and a curing catalyst, wherein the first thermally conductive filler comprises secondary particles wherein the primary particles are agglomerated, and the first thermally conductive filler satisfies the following formula 1: [Formula 1] 0.3 <A(m 2 / g) / B(µm)<3.0 Where A represents the specific surface area of the first thermally conductive filler and is a unitless value, and B represents the average particle size (D) of the first thermally conductive filler. 50 And it is a unitless value.
[0017] [Beneficial Effects] The silicone-based resin composition according to the present invention includes granular secondary particles in which primary particles are agglomerated as a first thermally conductive filler, and the ratio of the specific surface area to the average particle size of the first thermally conductive filler is greater than 0.3 and less than 3.0.
[0018] Therefore, the first thermally conductive filler included in the silicone-based resin composition can exhibit excellent thermal conductivity due to its large average particle size and large specific surface area.
[0019] Furthermore, the silicone-based resin composition exhibits thermal conductivity values that allow for proper heat dissipation even when commercially manufactured under different pressure conditions, and the small deviation in thermal conductivity of the silicone-based resin composition improves the reliability of product performance.
[0020] The cured product of the silicone-based resin composition according to the present invention can achieve high thermal conductivity, while having improved coverage and appropriate spread thickness.
[0021] Therefore, when the silicone-based resin composition is used in a semiconductor device, the silicone-based resin composition can be coated with a uniform thickness between the semiconductor package and the heat dissipation part, thereby improving the heat dissipation function. [Attached Image Description] Figure 1 This is a cross-sectional view showing the process of measuring the lap shear strength and joint separation length of a silicone-based resin composition.
[0023] Figure 2 This is a cross-sectional view showing a semiconductor device according to one embodiment.
Detailed Implementation Methods
[0025] In this specification or application, when a part “includes” a component, it means that the part may also include another component rather than exclude another component, unless there is no different disclosure. Furthermore, it should be understood that, unless otherwise stated, all numerical ranges of physical property values, dimensions, etc., of the components described in this specification or application are in all cases modified by the term “about”.
[0026] In this specification or application, it will be understood that when each part, surface, layer, or substrate is referred to as "above" or "below" another part, surface, layer, or substrate, that part, surface, layer, or substrate may be directly on or under the other part, surface, layer, or substrate, or may have an intermediate part, surface, layer, or substrate, and the criteria for "above" and "below" will be based on the accompanying drawings. Elements in the following drawings may be exaggerated, omitted, or shown schematically for convenience and clarity of explanation, and the dimensions of the elements do not perfectly reflect their actual dimensions.
[0027] The silicone-based resin composition and semiconductor device comprising the silicone-based resin composition according to the present invention will now be described.
[0028] The silicone-based resin compositions according to the present invention comprise organopolysiloxanes.
[0029] The organopolysiloxane can be represented by the following formula 1: [Formula 1] R 1 a SiO b In Equation 1, R 1 It may represent one or more groups selected from the group consisting of hydrogen atoms, hydroxyl groups and saturated or unsaturated monovalent hydrocarbon groups having 1 to 18 carbon atoms, and a may be about 1.8 to about 2.2. a+b may be about 3.5 to about 8.
[0030] a+b can be 4.
[0031] In Equation 1, R 1 The saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms can be, for example, alkyl, such as methyl, ethyl, propyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl or octadecyl; cycloalkyl, such as cyclopentyl or cyclohexyl; alkenyl, such as vinyl or allyl; aryl, such as phenyl or tolyl; aralkyl, such as 2-phenylethyl or 2-methyl-2-phenylethyl; or haloalkyl, such as 3,3,3-trifluoropropyl, 2-(perfluorobutyl)ethyl, 2-(perfluorooctyl)ethyl or p-chlorophenyl.
[0032] The organopolysiloxane may have a weight-average molecular weight of about 40,000 g / mol to about 80,000 g / mol, about 30,000 g / mol to about 100,000 g / mol, about 500 g / mol to about 10,000 g / mol, about 700 g / mol to about 7,000 g / mol, about 1,000 g / mol to about 5,000 g / mol, or about 1,500 g / mol to about 3,000 g / mol. The weight-average molecular weight may be measured based on polystyrene.
[0033] The kinematic viscosity of the organopolysiloxane at 25°C is 10 mm. 2 / s to 100,000 mm 2 / s, 20,000mm 2 / s to 100,000 mm 2 / s, or approximately 30 mm 2 / s to approximately 10,000 mm 2 / s. The kinematic viscosity of the organopolysiloxane can be measured at 25°C using an Ostwald viscometer.
[0034] Because the organopolysiloxane has a weight-average molecular weight and kinematic viscosity within the range described, it can maintain appropriate adhesion to the adherend and improve durability by preventing voids and cracks caused by thermal shock.
[0035] The organopolysiloxane may include a first organopolysiloxane.
[0036] The first organopolysiloxane includes an alkenyl group bonded to a silicon atom. A molecule of the first organopolysiloxane may contain at least two, two to ten, two to five, or two alkenyl groups.
[0037] The first organopolysiloxane can be represented by the following formula 2: [Equation 2] R 1 a R 2 c SiO b In Equation 2, R 1 It can be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 2 It can be alkenyl. In Formula 2, a+c can be about 1.8 to about 2.2, and a+b+c can be about 3.5 to about 8. In Formula 2, a+b+c can be about 4. In Formula 2, and a can be about 1.8 to about 2.2. Furthermore, c can be 0.0001 to 0.1.
[0038] The first organopolysiloxane can be represented by the following formula 3: [Formula 3] In Equation 3, R 1 It can be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 2 It can be alkenyl. Furthermore, in Formula 3, n can be 1 to 1,500, and m can be 0 to 20. In Formula 3, n can be 10 to 1,000, and m can be 0 to 20.
[0039] The first organopolysiloxane can be represented by the following formula 4: [Formula 4] In Equation 4, n can be from 1 to 1,500. n can be from 10 to 1,000.
[0040] The first organopolysiloxane may have a weight-average molecular weight (Mw) of about 500 g / mol to about 10,000 g / mol, about 700 g / mol to about 7,000 g / mol, about 1,000 g / mol to about 5,000 g / mol, or about 1,500 g / mol to about 3,000 g / mol. The weight-average molecular weight may be measured based on polystyrene.
[0041] The kinematic viscosity of the first organopolysiloxane at 23°C can be from 10 cP to 100,000 cP, from 30 cP to 50,000 cP, or from 10,000 cP to 40,000 cP. The kinematic viscosity of the first organopolysiloxane can be measured at 23°C using an Ostwald viscometer.
[0042] The organopolysiloxane may include a second organopolysiloxane.
[0043] The second organopolysiloxane may include hydrogen groups bonded to silicon atoms. The number of hydrogen groups per molecule of the second organopolysiloxane may be 1 to 10, 2 to 10, 2 to 5, or 2.
[0044] The second organopolysiloxane can be represented by the following formula 5: [Formula 5] In Equation 5, R 1 It can be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, R 3 It can be a hydrogen atom. Furthermore, in Equation 5, n can be 1 to 1,500, and m can be 0 to 20. In Equation 5, n can be 10 to 1,000, and m can be 0 to 20. In Equation 5, n can be 1 to 1,500, and m can be 0.
[0045] The second organopolysiloxane can be represented by the following formula 6: [Formula 6] The viscosity of the second organopolysiloxane at about 23°C can be about 500 cP to about 5,000 cP, about 500 cP to about 3,000 cP, or about 500 cP to about 2,000 cP.
[0046] The organopolysiloxane may further include a third organopolysiloxane. The third organopolysiloxane may be represented by the following formula 7: [Formula 7] In Equation 7, R 1It can be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 3 It can be a hydrogen atom. Furthermore, in Equation 7, n can be 1 to 1,500, and m can be 1 to 500. In Equation 7, n can be 10 to 1,000, and m can be 1 to 100.
[0047] The third organopolysiloxane can be represented by the following formula 8: [Formula 8] In Equation 8, n can be from 1 to 1,500, and m can be from 1 to 500. In Equation 8, n can be from 10 to 1,000, and m can be from 1 to 100.
[0048] The viscosity of the third organopolysiloxane at about 23°C can be about 50 cP to about 1,000 cP, about 100 cP to about 500 cP, or about 100 cP to about 500 cP.
[0049] The viscosity ratio of the first organopolysiloxane to the second organopolysiloxane can be from 10:1 to 40:1.
[0050] Furthermore, the viscosity ratio of the second organopolysiloxane to the viscosity of the third organopolysiloxane can be from 2:1 to 10:1.
[0051] Based on 100 parts by weight of total organopolysiloxane, the content of the first organopolysiloxane may be about 60 parts by weight to about 90 parts by weight, about 70 parts by weight to about 85 parts by weight, or about 75 parts by weight to about 85 parts by weight.
[0052] Based on 100 parts by weight of the first organopolysiloxane, the content of the second organopolysiloxane may be from about 10 parts by weight to about 40 parts by weight, from about 10 parts by weight to about 30 parts by weight, or from about 12 parts by weight to about 23 parts by weight.
[0053] Based on 100 parts by weight of the first organopolysiloxane, the content of the third organopolysiloxane may be from about 3 parts by weight to about 20 parts by weight, from about 3 parts by weight to about 15 parts by weight, or from about 4 parts by weight to about 10 parts by weight.
[0054] When the silicone-based resin composition comprises the first organopolysiloxane, the second organopolysiloxane, and the third organopolysiloxane within the range described, it can maintain appropriate adhesion to the substrate and spread evenly during the coating process.
[0055] The silicone-based resin composition includes a first thermally conductive filler.
[0056] Conventionally, spherical primary particles are used as thermally conductive fillers to improve the heat dissipation performance of silicone-based resin compositions. However, the small surface area of the thermally conductive filler reduces the contact characteristics between the powder particles, thus limiting its ability to achieve excellent heat dissipation performance.
[0057] To further improve heat dissipation performance, thermally conductive fillers are mixed with sheet-like or dendritic thermally conductive fillers having a large specific surface area. However, when the silicone resin composition contains the sheet-like and / or dendritic thermally conductive fillers, the dispersibility with the organopolysiloxane decreases, resulting in a significant reduction in coverage. Therefore, when the silicone-based resin composition is used as a thermally conductive layer in semiconductor devices, there is a problem of reduced contact area with the semiconductor package and heat sink, leading to deterioration in heat dissipation performance.
[0058] Therefore, the inventors have confirmed that when the first thermally conductive filler includes granular secondary particles in which the primary particles are agglomerated and the first thermally conductive filler satisfies the following Formula 1, it exhibits excellent thermal conductivity, improves the reliability of product performance due to small deviations in thermal conductivity under different pressure conditions, and exhibits improved coverage, strong adhesion strength, and appropriate joint separation length, thereby exhibiting excellent heat dissipation performance. [Formula 1] 0.3 <A(m 2 / g) / B(µm)<3.0 In Formula 1, A represents the specific surface area of the first thermally conductive filler and is a unitless value, and B represents the average particle size (D) of the first thermally conductive filler. 50 And it is a unitless value.
[0059] Generally, as the average particle size of thermally conductive fillers increases, the dispersibility can be improved, but the thermal conductivity may decrease due to the significant reduction in specific surface area.
[0060] However, the first thermally conductive filler according to the present invention comprises granular secondary particles in which the primary particles are agglomerated. Here, as long as the ratio of the specific surface area to the average particle size of the first thermally conductive filler satisfies Formula 1, it can have a larger specific surface area compared with other thermally conductive fillers having the same average particle size.
[0061] Therefore, the silicone-based resin composition including the first thermally conductive filler according to the present invention can achieve not only the excellent coverage characteristics of conventional spherical thermally conductive fillers, but also the excellent coverage characteristics of conventional sheet and dendritic thermally conductive fillers.
[0062] In Formula 1, A can be 0.8 m 2 / g to 2.0 m 2 / g, 0.8 m 2 / g to 1.8 m 2 / g, 0.8 m 2 / g to 1.6 m 2 / g, or 0.8 m 2 / g to 1.5 m 2 / g.
[0063] In Formula 1, B can be 0.5 µm to 10 µm, 0.5 µm to 5 µm, 0.5 µm to 4 µm, or 1 µm to 4 µm.
[0064] The average particle size is defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve derived from the thermally conductive powder using laser diffraction.
[0065] In Formula 1, A(m) 2 The ratio of (g) / B (µm) can be greater than 0.3 and less than 3.0, greater than 0.3 and less than 2.5, greater than 0.3 and less than 2.0, or greater than 0.4 and less than 2.0. When these ranges are met, excellent coverage characteristics, improved coverage, and appropriate spread thickness can be provided.
[0066] The primary particles can be flaky particles. When the primary particles are flaky particles, the mechanical strength of the secondary particles formed by the agglomeration of primary particles can be improved, thereby reducing the thermal conductivity deviation and further improving the reliability of product performance.
[0067] The first thermally conductive filler can be an aggregate of secondary particles composed of flake-shaped silver particles. The secondary particles may have a spherical shape.
[0068] The secondary particles can be formed by spray-drying the primary particles to agglomerate them, followed by firing.
[0069] The primary particles may have an average particle size (D) of 0.1 µm to 1 µm, 0.1 µm to 0.9 µm, 0.1 µm to 0.8 µm, or 0.1 µm to 0.5 µm. 50 ).
[0070] The first thermally conductive filler may have an aspect ratio of 0.5 to 3, 0.6 to 3, 0.6 to 2.8, 0.6 to 2.7, or 0.5 to 2.5.
[0071] The aspect ratio is defined as the length of the major axis of the first thermally conductive filler particle divided by the length of the minor axis of the first thermally conductive filler particle.
[0072] The first thermally conductive filler may have a density of 0.5 g / cm³. 3 Up to 6 g / cm 3 1 g / cm 3 Up to 6 g / cm 31.5 g / cm 3 Up to 6g / cm 3 or 2.5 g / cm 3 Up to 6 g / cm 3 The tap density.
[0073] To obtain the tap density, approximately 100 g of the first thermally conductive powder was weighed and gently poured into a 100 ml graduated cylinder using a funnel. The graduated cylinder was then placed on a tap density meter and compressed by dropping it 600 times at a drop height of 20 mm and a speed of 60 drops per minute. The tap density was calculated from the volume of the compressed thermally conductive powder.
[0074] Because the first thermally conductive filler includes granular secondary particles from which primary particles agglomerate, its mechanical properties may be greatly affected by the hardness of the first thermally conductive filler. The first thermally conductive filler may have a Mohs hardness of 2 to 5, 2 to 4.5, 2 to 4, 2 to 3, or 2.5 to 3. The Mohs hardness can be measured using a Mohs hardness tester. When the range is met, the phenomenon of significant deformation or breakage of the first thermally conductive filler due to multiple cracking during the pressurization process after the silicone-based resin composition has hardened can be minimized.
[0075] The first thermally conductive filler can be surface-treated with a surface treatment agent. The surface treatment agent may include C10 to C20 fatty acids. Examples of such fatty acids include decanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, myristone acid, palmitoleic acid, oleic acid, oleic acid, transoleic acid, isoleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, α-linolenic acid, etc.
[0076] The first thermally conductive filler may have a loss on ignition (Ig-loss) of less than about 0.8 wt%, less than about 0.7 wt%, less than about 0.6 wt%, less than about 0.5 wt%, less than about 0.4 wt%, less than about 0.3 wt%, less than about 0.2 wt%, or more than about 0.01 wt% and less than about 0.4 wt%. The loss on ignition may be measured at about 538°C for about 1 hour.
[0077] The surface of the first thermally conductive filler can be effectively treated even with a small amount of the surface treatment agent. That is, the first thermally conductive filler has a relatively low tap density and a large specific surface area, and can be surface-treated with a small amount of surface treatment agent. Therefore, the first thermally conductive filler can be uniformly dispersed in the organopolysiloxane and its thermal bonding can be improved. In other words, due to its improved dispersibility, the first thermally conductive filler can be added to the organopolysiloxane in a high concentration.
[0078] Based on 100 parts by weight of the organopolysiloxane, the silicone-based resin composition may contain the first thermally conductive filler in amounts of about 300 parts by weight to about 1,000 parts by weight, about 400 parts by weight to about 900 parts by weight, or about 500 parts by weight to about 800 parts by weight. When these ranges are met, adequate adhesion to the adherends can be maintained, and durability can be improved because voids and cracks caused by thermal shock do not occur.
[0079] The silicone-based resin composition may further include a spherical second thermally conductive filler having a shape different from that of the first thermally conductive filler. The second thermally conductive filler may be formed from spherical primary particles. Because the silicone-based resin composition includes the first thermally conductive filler containing granular secondary particles and the second thermally conductive filler containing spherical primary particles, the mechanical strength of the thermally conductive filler, which improves thermal conductivity, can be further improved, thereby reducing thermal conductivity deviation and improving product performance reliability.
[0080] The second thermally conductive filler may have an aspect ratio of 1 to 1.5, 1 to 1.45, 1 to 1.4, 1 to 1.35 or 1 to 1.3.
[0081] As the aspect ratio approaches 1, the shape of the second thermally conductive filler particles can be interpreted as almost spherical.
[0082] The aspect ratio is defined as the length of the major axis of the second thermally conductive filler particle divided by the length of the minor axis of the second thermally conductive filler particle.
[0083] The second thermally conductive filler may have a roundness of 0.95 to 1, 0.96 to 1, 0.97 to 1, or 0.98 to 1.
[0084] As the roundness approaches 1, the shape of the second thermally conductive filler particles can be interpreted as almost spherical.
[0085] The roundness can be calculated using the following formula: [Calculation Formula] Roundness = (4 × area) / (π × major axis length) 2 ) The second thermally conductive filler may have a thickness of 0.1 m. 2 / g to 1.0 m 2 / g, 0.1 m 2 / g to 0.9 m 2 / g, 0.1 m 2 / g to 0.8 m 2 / g, or 0.1 m 2 / g to 0.5 m 2 Specific surface area per g.
[0086] Regarding the weight ratio, the ratio of the first thermally conductive filler to the second thermally conductive filler can be 1:1 to 1:5, 1:1 to 1:4.5, 1:1 to 1:4, or 1:1 to 1:3. When these ranges are met, the cured product made from the silicone-based resin composition can achieve high thermal conductivity while having improved coverage and appropriate spread thickness.
[0087] Figure 1 This is a cross-sectional view showing the process of measuring the lap shear strength and joint separation length of a silicone-based resin composition.
[0088] Reference Figure 1 A silicone-based resin composition 30 with a thickness of approximately 200 µm is coated onto a region of a first nickel plate 20, and then a second nickel plate 10 is placed over the coated silicone-based resin composition 30. Next, the silicone-based resin composition 30 is cured at approximately 150°C for approximately 2 hours. The coating area of the silicone-based resin composition 30 can be approximately 2.5 cm × 1.25 cm. Then, the first nickel plate 20 and the second nickel plate 10 are pulled horizontally in opposite directions using a universal testing machine. Here, the horizontal stress on the first nickel plate 20 and the second nickel plate 10 is measured based on the length of the horizontal deformation.
[0089] The lap shear strength can be the maximum value of the stress applied to the first nickel plate 20 and the second nickel plate 10 divided by the coating area of the silicone-based resin composition 30.
[0090] The joint separation length can be the length at which the stress applied to the first nickel plate 20 and the second nickel plate 10 changes horizontally.
[0091] The lap shear strength of the silicone-based resin composition, as measured by DIN EN 1465, is 1 N / mm. 2 Or larger, 1.2 N / mm 2 or larger, 1.3 N / mm 2 or larger, 1.4 N / mm 2 Or larger, or 1.5 N / mm 2 Up to 2.5 N / mm 2 .
[0092] The joint separation length, as measured by DIN EN 1465, can be 0.3 mm or greater, 0.4 mm or greater, 0.5 mm or greater, or 0.5 mm to 1.0 mm.
[0093] When the specified range is met, both the adhesion stability and heat dissipation performance of the thermally conductive layer can be improved.
[0094] The shear modulus, expressed by the following formula, can be 1 N / mm. 3Or greater than but less than 3 N / mm 3 : [formula] Shear modulus (N / mm) 3 = LSS(N / mm) 2 ) / JSL(mm) Wherein LSS represents the lap shear strength of the silicone-based resin composition as measured by DIN EN 1465, and JSL represents the joint separation length of the silicone-based resin composition as measured by DIN EN 1465.
[0095] The shear modulus can be 1 N / mm². 3 Or greater than but less than 3 N / mm 3 1.1 N / mm 3 Or greater than but less than 3 N / mm 3 1.3 N / mm 3 Or larger and 2.5 N / mm 3 Or smaller, or 1.6 N / mm 3 Or larger and 2.5 N / mm 3 Or smaller.
[0096] When the specified range is met, deformation and peeling caused by shear stress can be suppressed, and deformation caused by external thermal shock can be easily recovered.
[0097] The coverage of the silicone-based resin composition, as measured by the following measurement method 1, can be 90% or greater, 92% or greater, 94% or greater, 96% or greater, or 99% or greater.
[0098] [Measurement Method 1] 1) The silicone-based resin composition is coated on a first silicone substrate having dimensions of 27 mm × 27 mm at a weight of 0.7 g.
[0099] 2) Place a second silicone substrate having the same or larger dimensions as the first silicone substrate on the coated silicone-based resin composition, and then allow the silicone-based resin composition to cure under a force of 3 kgf.
[0100] 3) Derive the area in which the first silicone substrate is in close contact with the second silicone substrate by the cured silicone-based resin composition.
[0101] 4) The coverage rate is the ratio of the area of the first silicone substrate and the second silicone substrate in close contact to the planar area of the first silicone substrate.
[0102] In addition, the thickness of the cured resin composition layer can be the spreading thickness.
[0103] Because the silicone-based resin composition has the above-mentioned coverage and spreading thickness, when the silicone-based resin composition is used as a thermally conductive layer for semiconductor devices, the thermally conductive layer can be in close contact with the semiconductor package and heat dissipation part over a large area, and can have high thermal conductivity.
[0104] The silicone-based resin composition may have a viscosity of 50,000 cP to 200,000 cP, 50,000 cP to 180,000 cP, 70,000 cP to 180,000 cP, or 70,000 cP to 150,000 cP.
[0105] The viscosity of the silicone-based resin composition can be measured at approximately 25°C using a rheometer MCR302 (manufacturer: Anton Paar GmbH) equipped with a plate of approximately 25 mm in diameter, according to the DIN EN ISO 3219 method. Here, a shear rate of approximately 10 (1 / s) can be applied to measure the viscosity.
[0106] When the specified range is met, appropriate coverage and spread thickness can be obtained.
[0107] The silicone-based resin composition may have a pot life of 10 to 16 hours, 10 to 15 hours, 10 to 14 hours, or 10 to 13 hours.
[0108] The applicable period can be measured by the following methods.
[0109] The silicone-based resin composition was allowed to stand at room temperature. Then, the time required for the viscosity of the silicone-based resin composition to increase by 50% compared to its initial viscosity was measured as the pot life.
[0110] The rate of change in thermal conductivity of the silicone-based resin composition, as measured by the following measurement method 2, is less than 30%. [Measurement Method 2] 1) The silicone-based resin composition was subjected to a temperature of 165°C and a pressure of 10 kgf / cm². 2 The first sheet was produced by hot-pressing under pressure for 15 minutes, and the silicone-based resin composition was separately subjected to heat treatment at 165°C and 0.1 kgf / cm². 2 The second sheet is produced by hot pressing under pressure for 15 minutes.
[0111] 2) The first sheet and the second sheet are cured at 150°C for 2 hours to produce the first sheet sample and the second sheet sample, respectively.
[0112] 3) Measure the thermal conductivity of the first sheet sample and the second sheet sample at 25°C according to ISO 22007-2.
[0113] 4) Calculate the rate of change of thermal conductivity using the following formula 2: [Formula 2] Rate of change of thermal conductivity (%) = (|TC) 10 – TC 0.1 │ / TC 10 ) × 100 In formula 2, where TC 10 It is the thermal conductivity (W / mK) of the first sheet sample, and TC 0.1 It is the thermal conductivity (W / mK) of the second sheet sample.
[0114] The rate of change of thermal conductivity of the silicone-based resin composition, as measured by method 2, may be less than 30%, 25% or less, 20% or less, 15% or less, or 10% or less.
[0115] Because the silicone-based resin composition exhibits the aforementioned rate of change in thermal conductivity, even when commercially used under different pressure conditions, the reliability of product performance can be ensured due to the small deviation in the rate of change in thermal conductivity. Furthermore, even when products manufactured using the silicone-based resin composition are subjected to thermal shock, they maintain appropriate adhesion to the adherends and prevent the occurrence of voids and cracks caused by thermal shock.
[0116] The ratio of the change in thermal conductivity of the silicone-based resin composition to the change in Shore A hardness, as measured by the following measurement method 3, can be 40% or less: [Measurement Method 3] 1) The silicone-based resin composition was subjected to a temperature of 165°C and 26 kgf / cm². 2 The sheet is manufactured by hot pressing under pressure for 15 minutes.
[0117] 2) The sheet is cured at 150°C for 5 minutes to produce a first cured product. The first cured product is subjected to Shore A hardness measurement according to ASTM D-2240 and thermal conductivity measurement at 25°C according to ISO 22007-2.
[0118] 3) The first cured product was cured at 150°C for 120 minutes to produce the second cured product. The second cured product was subjected to Shore A hardness measurement according to ASTM D-2240 and thermal conductivity measurement at 25°C according to ISO 22007-2.
[0119] 4) Calculate the relative ratio of the change in thermal conductivity to the change in Shore A hardness using the following formula: [formula] [(│TC H2 – TC H1 │) / (H2-H1)] × 100 Where H1 represents the Shore A hardness of the first cured product, H2 represents the Shore A hardness of the second cured product, and TC H1 This represents the thermal conductivity (W / mK) at H1, and TC H2 This represents the thermal conductivity (W / mK) in H2.
[0120] In the silicone-based resin composition, the relative ratio of the change in thermal conductivity to the change in Shore A hardness, as measured by measurement method 3, can be 35% or less, 30% or less, 25% or less, 20% or less, 10% or less, 5% or less, or 1% or less.
[0121] The hardness of products made from the silicone-based resin composition may vary depending on the curing temperature, curing time, or composition of the silicone-based resin composition.
[0122] Since the change in thermal conductivity of the silicone-based resin composition, as measured by the aforementioned measurement method, is 40% or less relative to the change in Shore A hardness, the change in thermal conductivity is significantly reduced compared to the change in hardness, exhibiting a thermal conductivity value that allows for proper heat dissipation. Furthermore, even if products made from the silicone-based resin composition exhibit hardness variations, the small change in thermal conductivity improves the reliability of its application in products requiring heat dissipation.
[0123] The cured products of the silicone-based resin compositions described in ASTM D-2240 may have a Shore A hardness of 95 or less, 85 or less, 75 or less, 65 or less, 60 or less, 10 to 60 or less, 20 to 60 or less, or 30 to 60 or less. When the hardness is within the range described, the occurrence of abrasion or cracking during product manufacturing can be minimized.
[0124] The silicone-based resin composition can satisfy the following formula: [formula] Y = 0.0169X + 6.5193 Where X represents the Shore A hardness of the cured product of the silicone-based resin composition according to ASTM D-2240, Y represents the thermal conductivity of the cured product of the silicone-based resin composition at 25°C according to ISO 22007-2, and Y is 6 W / mK to 8 W / mK.
[0125] The coefficient of determination (R) of X in the range of 3 to 57 2 It can be 0.95 or greater.
[0126] The formula represents a linear trend line with Shore A hardness as the variable X and thermal conductivity (which is the dependent variable based on X) as Y. This linear trend line can be exported using Microsoft Excel, and the coefficients (R0) can be determined. 2 The coefficient of determination, as a statistical term, is a well-known measure of the goodness of fit of a regression equation and represents the ratio of the sum of fluctuations of the data Yi of the dependent variable Y to the total sum of fluctuations. The coefficient of determination is usually expressed by R0. 2 This indicates that the goodness of fit of the regression equation increases as the coefficient of determination approaches 1.
[0127] For example, in the formula, Y is 6.6 to 7.4 in the range of X from 3 to 57, which means that the thermal conductivity is 6.6 W / mK to 7.4 W / mK in the range of Shore A hardness from 3 to 57. Here, the determination coefficient (R) 2 () indicates 0.95 or greater. Therefore, even with large changes in hardness, the change in thermal conductivity is relatively small, indicating a high goodness of fit of the regression equation. Thus, silicone-based resin compositions that satisfy the above formula can meet product performance reliability requirements even with changes in hardness due to small changes in thermal conductivity.
[0128] The silicone-based resin composition includes a curing catalyst.
[0129] The curing catalyst can accelerate the curing of the silicone-based resin composition.
[0130] Examples of curing catalysts include organotitanates such as platinum-divinyltetramethyldisiloxane complexes, tetrabutyl titanate, and tetraisopropyl titanate; organotitanium chelates such as diisopropoxybis(acetoacetate)titanium and diisopropoxybis(acetoacetate)titanium; organoaluminum compounds such as tri(acetylacetone)aluminum and tri(acetoacetate)aluminum; organozirconium compounds such as tetra(acetylacetone)zirconium and tetrabutyl zirconate; organotin compounds such as dibutyltin dioctanoate, dibutyltin dilaurate, and butyltin-2-ethylhexanoate; metal salts of organocarboxylic acids such as tin naphthenate, tin oleate, tin butyrate, cobalt naphthenate, and zinc stearate; amine compounds such as hexylamine and dodecylamine phosphate and their salts; quaternary ammonium salts such as benzyltriethylammonium acetate; lower fatty acid salts of alkali metals such as potassium acetate; dialkylhydroxylamines such as dimethylhydroxylamine and diethylhydroxylamine; and guanidine-containing organosilicon compounds.
[0131] Based on 100 parts by weight of the organopolysiloxane, the silicone-based resin composition may contain the curing catalyst in amounts of about 0.01 parts by weight to about 5 parts by weight, about 0.03 parts by weight to about 3 parts by weight, or about 0.1 parts by weight to about 2 parts by weight.
[0132] The silicone-based resin composition may also include a tackifier.
[0133] The tackifier may include alkoxysilanes. Furthermore, the tackifier may include epoxy groups. The tackifier may be at least one selected from the group consisting of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane.
[0134] Based on 100 parts by weight of the organopolysiloxane, the silicone-based resin composition may contain the tackifier in amounts of about 1 part to about 20 parts by weight, about 1 part to about 10 parts by weight, or about 2 parts to about 8 parts by weight. The tackifier can improve the adhesive strength between the organopolysiloxane and the thermally conductive filler.
[0135] The silicone-based resin composition may further include a reaction inhibitor. The reaction inhibitor may be at least one selected from the group consisting of alkynyl compounds, such as 2-methyl-3-butyn-2-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol; enynyl compounds, such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; curing reaction inhibitors, such as hydrazine compounds, phosphine compounds, and thiol compounds; etc.
[0136] Based on 100 parts by weight of the organopolysiloxane, the silicone-based resin composition may contain the reaction inhibitor in an amount of about 0.0001 parts by weight to about 10 parts by weight.
[0137] The method for preparing the silicone-based resin composition can be any known preparation method and is not particularly limited.
[0138] For example, the silicone-based resin composition can be prepared by mixing the organopolysiloxane, the thermally conductive filler, the curing catalyst, the tackifier, and the reaction inhibitor for 30 minutes to 4 hours using a mixer such as Trimix, Twinmix, and planetary mixer (all manufactured by Inoue Seisakusho Co., Ltd., registered trademark); Ultramixer (manufactured by Mizuho KogyoCo., Ltd., registered trademark); or Hibis Disper Mix (manufactured by Primix Co., Ltd., registered trademark). During the mixing process, the process temperature can be from about 0°C to about 25°C.
[0139] Figure 2 This is a cross-sectional view showing a semiconductor device according to an embodiment of the present invention.
[0140] Reference Figure 2 The semiconductor device according to the present invention includes a semiconductor package 200, a heat dissipation portion 400 disposed on the semiconductor package 200, and a thermally conductive layer 500 disposed between the semiconductor package 200 and the heat dissipation portion 400.
[0141] The semiconductor device may include a circuit board 100 and conductive bumps 300.
[0142] The circuit board 100 can support the semiconductor package 200, the conductive bump 300, the heat sink 400 and the thermal conductive layer 500.
[0143] The circuit board 100 may include circuit patterns. The circuit board 100 may include a plurality of circuit patterns disposed within a flat body comprising an insulating and heat-resistant material and having a predetermined strength. Furthermore, the circuit board 100 may include connection pads electrically connected to the circuit patterns and disposed on the body.
[0144] The main body of the circuit board 100 may include a thermosetting resin-based substrate, such as an epoxy resin substrate or a polyimide substrate, a flat plate, or a flat plate with a heat-resistant organic film such as a liquid crystal polyester film or a polyamide film attached. Circuit patterns may be arranged in a patterned shape within the main body and may include power wiring for power supply, ground wiring, and signal wiring for signal transmission. Each wiring may be configured to be separated from each other by multiple interlayer insulating films formed on the upper and lower surfaces of the main body.
[0145] The connecting pads can be exposed to the outside from the upper surface of the body and can be connected to the circuit pattern. Therefore, external connectors connected to the circuit board 100 can be electrically connected to the internal circuit pattern via the connecting pads.
[0146] Various electronic components can be mounted on connection pads included in the circuit board 100. The circuit board 100 can be a system board on which electronic components, including semiconductor packages 200, are mounted.
[0147] The semiconductor package 200 can be mounted on the circuit board 100. The semiconductor package 200 can be disposed on the circuit board 100. The semiconductor package 200 can be connected to the circuit board 100 via conductive bumps 300.
[0148] Semiconductor package 200 may include a semiconductor chip comprising an integrated circuit, a semiconductor package substrate connected to the semiconductor chip, conductive solder for connecting the semiconductor chip and the semiconductor package substrate, and a sealing portion for sealing the semiconductor chip and the conductive solder. The sealing portion may include a resin composition such as epoxy molding compound.
[0149] The semiconductor package 200 may be a memory device, a central processing unit, etc.
[0150] Conductive bumps 300 may be disposed between the semiconductor package 200 and the circuit board 100. Conductive bumps 300 can electrically connect the semiconductor package 200 and the circuit board 100 to each other. Conductive bumps 300 can be electrically connected to the semiconductor package 200 and the bonding pads.
[0151] A heat sink 400 may be disposed on the semiconductor package 200. The heat sink 400 may cover the semiconductor package 200. The heat sink 400 may be bonded to the circuit board 100. The heat sink 400 may cover the side surface of the semiconductor package 200.
[0152] The heat sink 400 may include a conductor. The heat sink 400 may include metal. The heat sink 400 may be thermally connected to an external heat sink.
[0153] The heat sink 400 protects the semiconductor package 200 from external physical impacts. The heat sink 400 also protects the semiconductor package 200 from external electromagnetic waves. In other words, the heat sink 400 blocks external electromagnetic waves.
[0154] A thermally conductive layer 500 may be disposed between the semiconductor package 200 and the heat sink 400. The thermally conductive layer 500 may directly contact the semiconductor package 200 and the heat sink 400. The thermally conductive layer 500 may be in close contact between the semiconductor package 200 and the heat sink 400.
[0155] The thermally conductive layer 500 can be thermally connected to the semiconductor package 200 and the heat sink 400. That is, the thermally conductive layer 500 can transfer the heat generated by the semiconductor package 200 to the heat sink 400.
[0156] The thickness of the thermally conductive layer 500 can be from about 1 µm to about 100 µm, from about 2 µm to about 70 µm, from about 5 µm to about 60 µm, or from about 10 µm to about 40 µm.
[0157] The thermally conductive layer 500 comprises a silicone-based resin composition. The silicone-based resin composition comprises an organopolysiloxane, a first thermally conductive filler, and a curing catalyst. The first thermally conductive filler comprises secondary particles from which primary particles have agglomerated. The first thermally conductive filler satisfies the following formula 1: [Formula 1] 0.3 <A(m 2 / g) / B(µm)<3.0 In Formula 1, A represents the specific surface area of the first thermally conductive filler and is a unitless value, and B represents the average particle size (D) of the first thermally conductive filler. 50 And it is a unitless value.
[0158] The silicone-based resin composition may be the same as the aforementioned silicone-based resin composition. Since the first thermally conductive filler in the silicone-based composition comprises secondary particles from which primary particles agglomerate, and the ratio of the specific surface area to the average particle size of the first thermally conductive filler, as expressed by Formula 1, satisfies a value greater than 0.3 and less than 3.0, the thermal conductivity of the thermally conductive layer 500 comprising the silicone-based composition can be improved. Furthermore, the thermally conductive layer 500 can maintain appropriate adhesion to the semiconductor package 200 and the heat dissipation portion 400, thus improving heat dissipation performance.
[0159] The method for manufacturing the semiconductor device can be any known manufacturing method, and there are no particular limitations.
[0160] First, the semiconductor package 200 can be mounted on the circuit board 100 via conductive bumps 300. Next, the silicone-based resin composition can be coated onto the semiconductor package 200. Alternatively, the silicone-based resin composition can be coated onto the lower surface of the heat sink 400.
[0161] Next, the heat dissipation portion 400 may cover the semiconductor package 200. Therefore, the coated silicone-based resin composition can directly contact the lower surface of the heat dissipation portion 400 and the upper surface of the semiconductor package 200, and the curable silicone resin composition can be cured at about 80°C or higher under a pressure of about 0.01 MPa or greater.
[0162] The pressure during the curing process can be about 0.01 MPa or greater. The pressure during the curing process can be about 0.05 MPa to about 100 MPa. The pressure during the curing process can be about 0.1 MPa to about 100 MPa.
[0163] The curing temperature can be from approximately 110°C to approximately 300°C. The curing temperature can be from approximately 120°C to approximately 300°C. The curing temperature can be from approximately 140°C to approximately 300°C. The curing time can be from approximately 30 minutes to approximately 20 hours. The thermally conductive layer 500 can be formed through this process.
[0164] The invention is described in more detail below with reference to embodiments and comparative examples. However, the embodiments and comparative examples below are merely examples for explaining the invention in more detail, and the invention is not limited to the embodiments and comparative examples below.
[0165] Example - Organopolysiloxane #1: A compound represented by Formula 4, having a viscosity of 20,000 cP at 23°C and containing an alkenyl group bonded to silicon: [Formula 4] - Organopolysiloxane #2: A compound represented by Formula 6, having a viscosity of 1,000 cP at 23°C and comprising a structure in which hydrogen groups are bonded to both ends: [Formula 6] - Organopolysiloxane #3: A compound represented by Formula 8, having a viscosity of 1,000 cP at 23°C and comprising a structure in which hydrogen groups are bonded to its side chains: [Formula 8] - Thermally conductive filler #1: granular silver powder, wherein the average particle size of the primary particles (D) 50 The particle size is approximately 0.3 µm and it agglomerates. The particulate silver powder has an average particle size (D) of approximately 2.5 µm. 50 (Approximately 2) Aspect ratio of length to diameter, approximately 2.5 m 2 Specific surface area per g and approximately 3 g / cm³ 3 tap density - Thermally conductive filler #2: granular silver powder, wherein the average particle size of the primary particles (D) 50 The particulate silver powder has an average particle size of about 5 µm and is agglomerated. 50 (Approximately 2) Aspect ratio of length to diameter, approximately 2 m 2 Specific surface area per g and approximately 5 g / cm³ 3 tap density - Thermally conductive filler #3: granular silver powder, wherein the average particle size of the primary particles (D) 50 The particulate silver powder has an average particle size of approximately 0.1 µm and is agglomerated. 50 (Approximately 2 aspect ratio, approximately 4 m) 2 Specific surface area per g and approximately 4.5 g / cm³ 3 tap density - Thermally conductive filler #4: granular silver powder, wherein the average particle size of the primary particles is (D 50 The particle size is approximately 0.4 µm and it agglomerates. The particulate silver powder has an average particle size (D) of approximately 6.5 µm. 50 (Approximately 1.5 aspect ratio, approximately 1.5 m) 2 Specific surface area per g and approximately 4 g / cm³ 3 tap density - Thermally conductive filler #5: Spherical silver powder with an average particle size of approximately 2.5 µm (D 50 (Approximately 1.1 aspect ratio, approximately 0.3m) 2 Specific surface area per g and approximately 6.4 g / cm³ 3 tap density - Thermally conductive filler #6: Flaky silver powder with an average particle size of approximately 1.2 µm (D 50 (Approximately 11 aspect ratio, approximately 0.4m) 2 Specific surface area per g and approximately 5 g / cm³ 3 tap density - Tackifier: 3-Glycidoxypropyltrimethoxysilane - Curing catalyst: Platinum-divinyltetramethyldisiloxane complex - Reaction inhibitor: 1-ethynyl-1-cyclohexanol Examples 1 to 6 and Comparative Examples 1 to 4 The silicone-based resin compositions were prepared by adding each of the compositions shown in Table 1 below to a planetary mixer and mixing them uniformly at room temperature for 1 hour at a speed of about 40 rpm.
[0166] [Table 1]
[0167] Experimental Example Experimental Example 1 – Measurement of Thermal Conductivity The silicone-based resin compositions of each of Examples 1 to 6 and Comparative Examples 1 to 4 were hot-pressed to a size of 30 mm × 30 mm × 4 mm. They were then cured at approximately 150°C for 2 hours to produce samples. The thermal conductivity of each sample of Examples 1 to 6 and Comparative Examples 1 to 4 was then measured at 25°C using a thermal conductivity analyzer (model name: TPS-2500S, manufacturer: Hot Disk AB) according to ISO 22007-2. The results are shown in Table 2 below.
[0168] Experimental Example 2 – Thermal Shock Test The silicone-based resin compositions of each of Examples 1 to 6 and Comparative Examples 1 to 4 were allowed to stand at -40°C for 30 minutes and then at 125°C for 30 minutes. This cycle was repeated approximately 500 times, and then the thermal conductivity was measured in the same manner as in Experimental Example 1. The results are shown in Table 2 below.
[0169] Experimental Example 3 – Measurement of Lap Shear Strength and Joint Separation Length The silicone-based resin compositions of each of Examples 1 to 6 and Comparative Examples 1 to 4 were coated to a thickness of about 200 µm onto an area of about 2.5 cm × 1.25 cm on a first nickel plate, and then covered with a second nickel plate. The first and second nickel plates were then pre-cured at 135°C for about 10 minutes under a weight compression of 3 kgf. Subsequently, the lap shear strength and joint separation length of the first and second nickel plates were measured according to DIN EN 1465 while being stretched in opposite directions using a universal testing machine (tensile strength analyzer, manufactured by ZwickRoell GmbH). The results are shown in Table 2 below.
[0170] Experimental Example 4 – Measurement of Coverage and Spread Thickness 0.7 g of each of Examples 1 to 6 and Comparative Examples 1 to 4 was coated onto a first silicone substrate having dimensions of approximately 27 mm × 27 mm, and then covered with a second silicone substrate having the same dimensions as the first silicone substrate. Next, the substrate was pre-cured at 135°C for approximately 10 minutes while applying a force of approximately 3 kgf. Then, it was cured at 150°C for approximately 2 hours. The areas of close contact between the first and second silicone substrates and the cured coating were measured using a SAT ultrasonic inspection device and an image particle analyzer, and the ratio of the contact area to the total planar area was derived. The results are shown in Table 2 below.
[0171] Experimental Example 5 – Viscosity Measurement The viscosity of the silicone-based resin compositions of Examples 1 to 6 and Comparative Examples 1 to 4 was measured at approximately 25°C using a rheometer (product name: MCR302, manufacturer: Anton Paar GmbH) with a circular plate of 25 mm diameter, according to the method of DIN EN ISO 3219. Here, the viscosity was measured at a shear rate of approximately 10 (1 / s). The results are shown in Table 2 below.
[0172] Experimental Example 6 - Measurement of Service Life The silicone-based resin compositions of each of Examples 1 to 6 and Comparative Examples 1 to 4 were allowed to stand at room temperature, and the time required for the viscosity to increase by 50% compared to the initial viscosity was measured. The results are shown in Table 2 below.
[0173] [Table 2]
[0174] Experimental Example 7 – Measurement of the Rate of Change in Thermal Conductivity The silicone-based resin compositions of each of Examples 1 to 6 and Comparative Examples 1 to 4 were hot-pressed at 165°C under the pressure conditions shown in Table 3 below to produce sheets. The sheets were then cured at 150°C for 2 hours, and samples with a width of 30 mm, a length of 30 mm, and a thickness of 4 mm were then manufactured. The thermal conductivity of the samples manufactured in Examples 1 to 6 and Comparative Examples 1 to 4 was then measured at 25°C using a thermal conductivity analyzer (model name: TPS-2500S, manufacturer: Hot Disk AB) according to the ISO 22007-2 method. The results are shown in Table 3 below.
[0175] [Table 3]
[0176] Referring to Tables 1 to 3, the silicone-based resin compositions of Examples 1 to 6 include particulate thermally conductive powder in which primary particles are agglomerated, and the specific surface area of the thermally conductive powder is related to the average particle size (D). 50 The ratio of () to () is greater than 0.3 and less than 3.0.
[0177] Therefore, it can be confirmed that the silicone-based resin compositions of Examples 1 to 6 possess excellent thermal conductivity, improved coverage, relatively strong adhesive strength, and appropriate joint separation length, while having the same thermally conductive filler content as the silicone-based resin compositions of Comparative Examples 1 to 4. Furthermore, since the silicone-based resin compositions of Examples 1 to 6 exhibit a low rate of change in thermal conductivity, it can be confirmed that they perform appropriate heat dissipation functions and demonstrate improved product performance reliability even when manufactured for commercial purposes under different pressure conditions.
[0178] [Symbol Explanation] 10: Second nickel plate 20: First nickel plate 30: Silicone-based resin composition 100: Circuit board 200: Semiconductor package 300: Conductive bump 400: Heat dissipation section 500: Thermal conductive layer
Claims
1. A silicone-based resin composition comprising: Organopolysiloxanes; First thermally conductive filler; as well as Solidified catalyst, The first thermally conductive filler includes secondary particles formed by the agglomeration of primary particles. The first thermally conductive filler satisfies the following formula 1: [Formula 1] 0.3 < A(m 2 / g) / B(µm) < 3.0 Where A represents the specific surface area of the first thermally conductive filler and is a unitless value, and B represents the average particle size (D) of the first thermally conductive filler. 50 And it is a unitless value.
2. The silicone-based resin composition according to claim 1, wherein the primary particles are flake-shaped particles.
3. The silicone-based resin composition according to claim 1, wherein the first thermally conductive filler has an aspect ratio of 0.5 to 3.
4. The silicone-based resin composition according to claim 1, wherein the first thermally conductive filler has a content of 0.5 g / cm³. 3 Up to 6 g / cm 3 The tap density.
5. The silicone-based resin composition according to claim 1, wherein the silicone-based resin composition further comprises a spherical second thermally conductive filler different from the first thermally conductive filler.
6. The silicone-based resin composition according to claim 5, wherein the second thermally conductive filler has an aspect ratio of 1 to 1.
5.
7. The silicone-based resin composition according to claim 5, wherein the weight ratio of the first thermally conductive filler to the second thermally conductive filler is 1:1 to 1:
5.
8. The silicone-based resin composition according to claim 1, wherein the lap shear strength of the silicone-based resin composition, measured by DIN EN 1465, is 1 N / mm. 2 Or larger.
9. The silicone-based resin composition according to claim 1, wherein the coverage of the silicone-based resin composition, as measured by the following measurement method 1, is 90% or greater: [Measurement Method 1] 1) The silicone-based resin composition is coated at a weight of 0.7 g onto a first silicone substrate having dimensions of 27 mm × 27 mm. 2) Place a second silicone substrate having the same or larger dimensions as the first silicone substrate onto the coated silicone-based resin composition, and then allow the silicone-based resin composition to cure under a compressive force of 3 kgf. 3) Derive the area where the first silicone substrate is in close contact with the second silicone substrate by the cured silicone-based resin composition, and 4) The coverage rate is the ratio of the area of the first silicone substrate and the second silicone substrate in close contact to the planar area of the first silicone substrate.
10. The silicone-based resin composition according to claim 1, wherein the rate of change of thermal conductivity of the silicone-based resin composition, as measured by the following measurement method 2, is less than 30%: [Measurement Method 2] 1) The silicone-based resin composition was subjected to a temperature of 165°C and a pressure of 10 kgf / cm². 2 The first sheet was produced by hot pressing under pressure for 15 minutes, and the silicone-based resin composition was separately subjected to heat treatment at 165°C and 0.1 kgf / cm². 2 The second sheet is manufactured by hot pressing under pressure for 15 minutes. 2) The first sheet and the second sheet are cured at 150°C for 2 hours to produce a first sheet sample and a second sheet sample, respectively. 3) The thermal conductivity of the first sheet sample and the thermal conductivity of the second sheet sample were measured at 25°C according to ISO 22007-2. 4) Calculate the rate of change of thermal conductivity using the following formula 2: [Formula 2] Rate of change of thermal conductivity (%) = (|TC) 10 – TC 0.1 │ / TC 10 ) × 100 Among them TC 10 It is the thermal conductivity (W / mK) of the first sheet sample, and TC 0.1 It is the thermal conductivity (W / mK) of the second sheet sample.
11. A semiconductor device, comprising: Semiconductor packages; A heat dissipation portion disposed on the semiconductor package; as well as A thermally conductive layer is placed between the semiconductor package and the heat dissipation section. The thermally conductive layer comprises a silicone-based resin composition. The silicone-based resin composition comprises an organopolysiloxane, a first thermally conductive filler, and a curing catalyst. The first thermally conductive filler includes secondary particles formed by the agglomeration of primary particles, and The first thermally conductive filler satisfies the following formula 1: [Formula 1] 0.3 < A(m 2 / g) / B(µm) < 3.0 Where A represents the specific surface area of the first thermally conductive filler and is a unitless value, and B represents the average particle size (D) of the first thermally conductive filler. 50 And it is a unitless value.
Citation Information
Patent Citations
Thermally conductive silicone grease composition
KR1020200086307A